Columnar Propeller‐Like 1, 3, 5‐Triphenylbenzenes: Probing the Effect of Chlorine on the Suzuki Cross‐Coupling and Liquid Crystalline Properties. Issue 15 (25th February 2020) - Grunwald, Marco André; Wöhrle, Tobias; Forschner, Robert; Baro, Angelika; Laschat, Sabine
Abstract : Suzuki cross‐couplings either between chlorinated N ‐methyliminodiacetic acid (MIDA)‐protected aryl boronates and 1, 3, 5‐tribromobenzene or between chlorinated aryl bromides and phenyltrisboronic species to star‐shaped 1, 3, 5‐triphenylbenzenes with different substitution patterns and chloro substituents at the outer phenyl rings were studied. The chlorinated precursors required for the respective reaction were synthesized and characterized. Depending on the used coupling reaction target triphenylbenzenes were isolated in yields between 42 % and 88 %. Their mesomorphic properties were influenced by the substitution pattern and number of peripheral chlorine atoms. Triphenylbenzene with 3, 5‐alkoxy substitution and H in para ‐position self‐assembled into either columnar hexagonal (Colh ) mesophases or a soft crystal. While threefold chloro substitution in meta ‐position of the outer phenyl rings led to stable room temperature Colho phases, triphenylbenzenes with threefold para ‐chloro or 3, 5‐dichloro substitution were non‐mesomorphic. Based on X‐ray diffraction data a helical packing model for the observed phases similar to that of related alkoxy‐substituted triphenylbenzenes was proposed. Abstract : Two variants of the Suzuki–Miyaura cross‐coupling (A and B) allow the synthesis of (poly)chlorinated shaped‐persistent hekates. Method B was found to be superior to A improving the yields up to 88 %. Liquid crystalline properties of some hekates were observed.